Epidural morphine analgesia in Guillain Barré syndrome. Issue 8 (August 1989) - Genis, D; Busquets, C; Manubens, E; Dávalos, A; Baró, J; Oterino, A
Abstract : Severe pain is a frequent symptom in the Guillain Barré syndrome and can be intense, long lasting and with no response to the usual analgesics, including parenteral opiates. Epidural analgesia using morphine chloride in low doses has satisfactorily relieved pain in this disease in nine patients.